Identification and validation of genes encoding humoral specificity for the chemical allergen toluene diisocyanate - Adam V. Wisnewski; Jian Liu (PLoS ONE, 2026)
A panel of hybridomas specific for different isomers of toluene diisocyanate (TDI), a cross‑linking chemical used in polyurethane production, has been previously described. These hybridomas were originally developed by researchers at the USA’s National Institute for Occupational Safety and Health (NIOSH). We sought to determine the DNA sequence encoding these TDI-specific monoclonal antibodies, enabling identification of germline gene rearrangement resulting in chemical specificity as well as production of the mAbs recombinantly. B cell receptor sequencing (BCR-seq) of hybridoma RNA readily identified productive heavy and light chain antibody sequences. The productive light chains of all 7 hybridomas showed strong identity with different genomic variable (V) and joining (J) region sequences with few changes from germline configuration. However, the productive heavy chains contained more substantial changes in their genomic V and J-region sequences consistent with antigen-driven affinity maturation, as well as N- and P- nucleotide additions comprising their complementarity-determining region 3 (CDR3). The hybridoma-defined TDI-specific mAbs were subsequently produced recombinantly in a human embryonic kidney cell line expression system, purified, and tested for their binding capacity against albumin derivatized with TDI, related diisocyanates, and control antigen. The recombinant versions of the TDI-specific mAbs demonstrated binding capacity for different isomers (2,4 and 2,6) of TDI consistent with that previously reported for the hybridoma secreted clones; one specific for 2,4-TDI, one specific for 2,6-TDI, three that bind both 2,4- and 2,6-TDI, and two that show cross-reactivity with 4,4′‑methylene diphenyl diisocyanate (MDI). None of the recombinant mAbs bound to aliphatic hexamethylene diisocyanate (HDI), its oligomer, or control antigen. Additional recombinant versions of the TDI mAbs, with identical V-regions, but different C-regions, demonstrated the dependence of antigen specificity on the V-region, but also highlighted the potential for C-region sequence to affect their detection in ELISA assays. The DNA sequences defined herein may be useful to other investigators wishing to generate recombinant TDI-specific mAbs as detection reagents for research or as standards for clinical serology tests.